The economic partnership agreements with Africa: Macroeconomic impacts and pro-developmental policy responses - Bernhard Tröster; Hannes Grohs; Jan Grumiller; Werner Raza; Cornelia Staritz; Rudi von Arnim (Austrian Foundation for Development Research (ÖFSE), 2018)
The Economic Partnership Agreements (EPAs) between the EU and African, Caribbean and Pacific (ACP) countries mark a new era in the economic relations between both sides. Reciprocal tariff liberalization will however result in asymmetric market opening by ACP partners, which will entail negative, though small, macroeconomic effects for these countries in the short to medium term. In order to deliver upon the promised tangible benefits of EPAs in the longer term, the EU should implement strong policy responses in three key areas: (i) coping with adjustment costs, (ii) promoting productive development, and (iii) fostering trade-related institutional capacities in the public sector and civil society, including an effective monitoring process for EPA implementation.
Keywords: 330